The mediating effect of the employee commitment on the relationship between recruitment process and organizational performance in UAE organisations - Ali Jafar Al Ansaari, Omar Ibrahim (2022)
The UAE employment market has a higher rate of turnover; besides some studies revealed that the recruitment process is slow and weakly prepared. The high rate of turnover can negatively affect the organizations’ performance in the UAE; therefore, revealing the causes can contribute to overcoming the problem and avoiding the weak recruitment practices, which will improve the performance and strengthen the UAE economy. Therefore, this study is an empirical examination by surveying the 34 companies of the Fujairah National Group (FNG) to examine the mediating role of employee commitment on the relationship between the recruitment process and organizational performance. Social exchange theory (SET) assumes that encouragement activities undertaken between an organization and its employees generate organizational commitment. The proposed conceptual model has the recruitment process as the independent variables, employees’ commitment as the mediating variable, and organizational performance as the dependent variables. The quantitative research approach has been used, and the study applied a cross-sectional survey method; and the unit of analysis of this study is the companies of the Fujairah National Group (FNG), which includes 34 working companies. The population of the study is the employees who involve in the recruitment and selection process in all companies. This includes human resource employees, besides supervisors, managers, and senior managers in all departments, and the estimated population is 1075. The technique used for this study is quota sampling because the population is classified into nine different quotas. The face-to-face direct collection is applied by visiting the target companies and asks the available participants on the chosen companies to fill up a printed copy of the questionnaire. The final valid data set has 366 respondents. The proposed model of this particular study has four regression models, in which 15 relationships are tested by using the significance level value with the path coefficient analysis. Overall, 12 hypotheses are accepted, and three are rejected. The three rejected hypotheses are related to the variable job analysis. Future work is advised to explore why the job analysis is not an antecedent of organizational performance in the UAE.